Linking electronic word-of-mouth about films, destination familiarity, and destination brand image with choice intention of film-featured destinations - Dang Thi Thanh , Hien; Tran Le , Phong; Nguyen Hoai Phuong , Uyen; Huynh Thi Quynh , Chau; Vo Thi Quynh , Nga (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
This study aims to explore the relationship between online word-of-mouth (eWOM) about movies, destination familiarity, and destination brand image with the intention of choosing film-featured destinations based on the Stimulus-Organism-Response (S-O-R) model. The research was conducted on 499 Vietnamese respondents who watched movies and read online reviews about them. The findings show that eWOM about movies can increase the intention to choose film-featured destinations through three pathways: (i) increasing destination familiarity, (ii) reinforcing destination brand image, and (iii) enhancing the resonance between destination familiarity and destination brand image. This study contributes new theoretical insights into the role of eWOM about movies in shaping tourists’ behavioral intentions toward film-featured destinations. It also provides managerial implications for destination management organizations and tourism businesses in the growing trend of film-induced tourism.